Perancangan dan Implementasi Role Model pada Ruang Kerja dengan Konsep 5S di PT Jindal Stainless Indonesia - Felix Surya Wiranata; Prayonne Adi (Jurnal Titra, 2022)
PT. Jindal Stainless Indonesia is a manufacturing company in the stainless steel industry which is currently in the process of making improvements to the 5S work culture. Improvements began in the workspace by designing a role model in workspace with 5S concept. 5S is a method originating from Japan that aims to organize and maintain an intensive work area. The design of the workspace role model with the 5S concept is carried out in the workspace of the SHE and HRD Department. The seiri stage is the activity of selecting and sorting items in each area of the workspace. The seiton stage is an activity to tidy up existing items. The seiso stage is an activity to clean the space and work area. The seiketsu stage is an activity of applying the 5S standard. The shitsuke stage is a 5S discipline activity. With the workspace role model that has been created, the implementation of 5S in other workspaces will be easier. The result of designing and implementing a workspace role model with the 5S concept is the existence of a workspace role model with the 5S concept that can be used as a reference in implementing 5S in the workspace.